Bibliometric Analysis of Sources for Nature Based Solutions, Building Integrated and Green Systems and Green Roofs - Bekou Evangelia; Matsouki Niki; Zervas Efthimios (E3S Web of Conferences)
The objective of this study is to analyse the scientific production of “Nature Based Solutions”, “Building Integrated and Green Systems” and “Green Roofs”, collected with Scopus database. The bibliometric analysis was performed for the Number of Publications and Citations per Year, the Document and Source Type, the Source Title, the Affiliation, the Country, the Scientific Field and the Keywords used. The majority of the relative works published during the last decade concern Green Roofs (GR, 52% of the works), and Nature Based Solutions (NBS, 44% of the works), and only 4% deal with Building Integrated and Green Systems (BIGS). Key findings feature United States and United Kingdom as the main contributors in all those three areas, while China’s interest in the areas of GR and BIGS is constantly increasing during last years. The results show that the major Scientific Field in NBS and GR is the Environmental Science, while in BIGS is Engineering. The keyword analysis reveals that all three subject areas are investigating the impact on climate change, carbon dioxide emission and sequestration, water conservation, environmental impact and management, sustainable development and urban planning.